Comparison of Neutrophil-to-Lymphocyte Ratio and Platelet to-Lymphocyte Ratio Before and After Chemotherapy on the Prognosis of Nasopharyngeal Carcinoma Patients - Rahim, Rita; Djufri, Nani Iriani; Djamin, Riskiana; Qanitha, Andriany (Asian Pacific Journal of Cancer Biology, 2026)
Background: The neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) have emerged as reliable systemic inflammatory markers associated with cancer progression and prognosis. Their prognostic role in nasopharyngeal carcinoma (NPC) remains of significant clinical interest, particularly in evaluating treatment response to chemotherapy. This study aimed to compare NLR and PLR values before and after chemotherapy and to analyze their relationship with prognosis in patients with NPC. Methods: A total of 100 NPC patients who met the inclusion criteria were enrolled. NLR and PLR values were calculated from peripheral blood samples obtained before and after three cycles of chemotherapy. Statistical analyses were performed using the Wilcoxon signed-rank test to compare pre- and post-treatment values and the Chi-square test to assess their association with prognosis. Results: Median NLR decreased significantly from 3.2 (0.2–16.4) pre-treatment to 1.9 (0.5–8.3) post-treatment (p < 0.001), and median PLR decreased from 185.9 (23.1–741.7) to 150.4 (67.8–270.2) (p < 0.001). Stage-stratified analysis revealed significant reductions in NLR and PLR in patients with stage II–IVA disease (p < 0.05), whereas stage IVB patients showed non-significant decreases. Patients with lower post-treatment NLR and PLR values were more likely to have a favorable prognosis, with 72.7–73.7% of stage II–III patients classified as good prognosis versus only 16.7–20.0% in stage IVB. Conclusion: Three cycles of chemotherapy significantly reduced systemic inflammation markers NLR and PLR in stage II–IVA NPC, with reductions correlating with improved short-term prognosis. Persistently elevated NLR and PLR in stage IVB patients suggest ongoing systemic inflammation and potential chemoresistance. NLR and PLR are practical, cost-effective biomarkers for monitoring treatment response and predicting prognosis in NPC.